2016
DOI: 10.1111/nep.12583
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction reduces perlecan at mid‐metanephrogenesis in rats

Abstract: Maternal protein restriction reduced the expression of perlecan and lead aberrant cell proliferation and apoptosis during mid-metanephrogenesis in offspring. This data may provide new evidence to understand the mechanism of reduced nephron number due to maternal protein restriction and enlighten solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For decades it has been known that exposure to dietary protein restriction in utero may result in a reduction in nephron number in offspring (Boubred et al, 2016; Hoppe, Evans, Moritz, et al, 2007; Hoppe, Evans, Bertram, & Moritz, 2007; Langley & Jackson, 1994; Langley‐Evans, 1997; Langley‐Evans, Welham, & Jackson, 1999; Nwagwu, Cook, & Langley‐Evans, 2000; Tang, Shen, Chen, Zha, & Xu, 2016; Woods et al, 2001; Woods & Weeks, 2004; Yu et al, 2019; Zimanyi et al, 2006), but the timing of this developmental deficit and the molecular mechanisms involved are still poorly understood. The major findings from the present study were: (a) there was no effect of either maternal diet or sex on branching morphogenesis at E14.25; (b) nephron number at E17.25 was 14% lower in male and female LP offspring than in NP controls; (c) at E14.25, expression levels of genes involved in branching morphogenesis and nephrogenesis were similar in the dietary groups, but significant differences between sexes were identified; and (d) at E17.25, expression levels of several genes involved in branching morphogenesis and nephrogenesis were lower in LP offspring than NP offspring in both male and female offspring.…”
Section: Discussionmentioning
confidence: 99%
“…For decades it has been known that exposure to dietary protein restriction in utero may result in a reduction in nephron number in offspring (Boubred et al, 2016; Hoppe, Evans, Moritz, et al, 2007; Hoppe, Evans, Bertram, & Moritz, 2007; Langley & Jackson, 1994; Langley‐Evans, 1997; Langley‐Evans, Welham, & Jackson, 1999; Nwagwu, Cook, & Langley‐Evans, 2000; Tang, Shen, Chen, Zha, & Xu, 2016; Woods et al, 2001; Woods & Weeks, 2004; Yu et al, 2019; Zimanyi et al, 2006), but the timing of this developmental deficit and the molecular mechanisms involved are still poorly understood. The major findings from the present study were: (a) there was no effect of either maternal diet or sex on branching morphogenesis at E14.25; (b) nephron number at E17.25 was 14% lower in male and female LP offspring than in NP controls; (c) at E14.25, expression levels of genes involved in branching morphogenesis and nephrogenesis were similar in the dietary groups, but significant differences between sexes were identified; and (d) at E17.25, expression levels of several genes involved in branching morphogenesis and nephrogenesis were lower in LP offspring than NP offspring in both male and female offspring.…”
Section: Discussionmentioning
confidence: 99%
“…These could be explained by increased apoptosis in nephron progenitors during the active glomerular formation period resulting in a nephron deficit. Our previous work showed that there are massive amounts of glomerular development and elevated levels of cell apoptosis during the late gestational and early postnatal periods in IUGR rat ( Tang et al, 2016 ). Interestingly, the differentially expressed endorepellin identified by comparative proteomics was significantly reduced in the mid and late stages of IUGR kidney development, and it was mainly expressed in the extracellular matrix of the metanephric cell and the periphery of the ureteric bud ( Shen et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous comparative proteomic studies identified that perlecan was significantly decreased in the kidney development of the IUGR animal model and was associated with cell apoptosis ( Welham et al, 2002 ; Li et al, 2010 ; Tafti et al, 2011 ). Perlecan, encoded by the HSPG2 gene, is a heparan sulfate proteoglycan (HSPG) in the extracellular matrix around the metanephric mesenchyme and mainly produced by epithelial cells of the ureteric bud ( Tang et al, 2016 ). Endorepellin is the C-terminal domain of perlecan and can be cleaved into a soluble form by using cathepsin L. Other cell and organ experiments have confirmed that endorepellins inhibit nearby cell apoptosis through the activation of ERK1/2-dependent anti-apoptotic pathways ( Raymond et al, 2004 ; Laplante et al, 2006 ; Lee et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%